Pengembangan Buku Panduan Bimbingan Kelompok Berlandaskan Teori Ginzberg Dengan Teknik Permainan Simulasi Untuk Meningkatkan Eksplorasi Karir Siswa - Ni Wayan Devis Wati Devis; Nyoman Dantes; Luh Putu Sri Lestari (Jurnal Bimbingan dan Konseling Indonesia, 2023)
This research is a research and development. “This guidebook was created to be used as a reference for Counseling Guidance teachers in carrying out counseling services in schools to improve student career exploration. The development procedure in this study uses the 4-D modification learning tool proposed by Thiagarajan, namely define, design, development, and disseminate. This study involved the subjects of 5 experts in counseling guidance including 3 lecturers of Counseling Guidance FIP Undiksha and 2 teachers of Counseling Guidance at SMP Negeri 2 Kediri to test the validity of the contents of the product and 15 Counseling Guidance teachers to test the acceptance of the product. To test the effectiveness of the guidebook, researchers involved 8 students as subjects. Of the 22 instrument items used in the assessment by experts, all items of the guidebook have good validity. Based on this assessment, it was found that the content validity index (CVI) of the category guidebook was very appropriate. In the acceptance test of products using PAIT analysis, a mean persentil of 98 was obtained which was categorized as A (Very Practical) so that the guidebook was feasible to use. Hypothesis testing shows that the Implementation of the A Group Guidance Guidebook Based on Ginzberg’s Theory With Effective Simulation Game Techniques to Improve Students’ Career Exploration with a count of 12.979 with a significance level of 0.05 and an ES value = 4.588 which means the effect of the guidebook to improve the career exploration of high-category students.” Abstrak: Penelitian ini yakni penelitian pengembangan. Buku acuan ini di bentuk guna bisa di jadikan pedoman bagi guru BK ketika menjalankan layanan konseling di sekolah untuk meningkatkan eksplorasi karir siswa. Prosedur pengembangan dalam penelitian ini menggunakan perangkat pembelajaran modifikasi 4 – D yang di kemukakan oleh Thiagarajan yakni : “(1) Tahap Pendefinisian,(2) Tahap Perancangan, (3) Tahap Pengembangan, (4) Tahap Penyebaran. Penelitian ini menyangkutkan subjek 5 orang ahli dalam Bimbingan Konseling(BK) yakni 3 orang dosen BK FIP Undiksha dan 2 orang guru BK SMP Negeri 2 Kediri guna menguji validitas isi produk dan 15 orang guru BK guna mengujikan keberteriman produk. guna ujikeefektifitasan buku panduan, pengkaji menyangkut 8 orang siswa selaku subjek. Dari 22 butir instrumen yang di pakai pada penilaian oleh pakar/ahli, seluruh butir buku panduan mempunyai validitas yang baik. Berlandaskan penilaian ini di peroleh indeks validitas isi buku acuan bergolongan sangat sesuai.” Pada uji keberterimaan produk yang memakai analisa PAIT di peroleh mean persentil sejumlah 98 yang bergolongan A (Sangat Praktis) maka buku panduan layak di pakai. Uji hipotesis membuktikan bila Implementasi Buku Panduan Bimbingan Kelompok Berlandaskan Teori Ginzberg Dengan Teknik Permainan Simulasi Efektif Untuk menaikan Eksplorasi Karir Siswa Teori dengan thitung 12,979 terhadap tingkat signifikansi 0,05 dan nilai ES= 4,588 yang berarti efek dari buku panduan untuk menaikan eksplorasi karir siswa bergolongan tinggi.